2002
DOI: 10.1046/j.1463-5224.2002.00217.x
|View full text |Cite
|
Sign up to set email alerts
|

Causes of uveitis in dogs: 102 cases (1989–2000)

Abstract: Uveitis is one of the most common ocular diseases and one of the most common causes of blindness in dogs. The purpose of this retrospective study was to correlate the signalment, history, clinical signs and ophthalmic findings of dogs with uveitis with the underlying etiology. We conducted a retrospective study of 102 dogs presented to the NCSU-VTH from 1989 to 2000 with clinical signs of uveitis. Medical records of dogs presented for uveitis were reviewed. Dogs were included in the study only if a complete di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
52
2
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 17 publications
3
52
2
4
Order By: Relevance
“…The prevalent cause of uveitis was trauma in 50% of cases, followed by infection in 40% (80% ehrlichiosis and 20% leptospirosis) and autoimmune disease in 10% (uveodermatologic syndrome). The causes of uveitis usually include inflammatory processes and autoimmune, infectious and traumatic diseases, among others (MASSA et al, 2002;TOWNSED, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalent cause of uveitis was trauma in 50% of cases, followed by infection in 40% (80% ehrlichiosis and 20% leptospirosis) and autoimmune disease in 10% (uveodermatologic syndrome). The causes of uveitis usually include inflammatory processes and autoimmune, infectious and traumatic diseases, among others (MASSA et al, 2002;TOWNSED, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The glaucoma is characterized by increased IOP with resultant retinal and optic disk dysfunction and the main clinical signs are dilated pupil, bulbar conjunctival venous congestion, corneal edema, blepharospasm, buphthalmos and partial or complete loss of vision . The uveitis is an inflammation of the iris and ciliary body that often leads to the reduction of IOP and the main clinical signs are red eye, miosis, photophobia, blepharospasm, pain, epiphora, hypopyon, hyphema, episcleral vascular injection and corneal edema (MASSA et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Results of 1 prospective study 2 of 94 dogs with multicentric lymphoma indicated that 35 (37%) of those animals had signs of ocular disease; the most common finding was anterior uveitis, which was detected in 25 of 35 (71%) dogs with ocular involvement. Likewise, results of a retrospective study 37 of 102 dogs with anterior uveitis indicated that lymphoma was the most common neoplastic cause of that problem (approx 10% of animals). However, in both of those studies, 2,37 all dogs with lymphoma also had signs of nonocular disease.…”
Section: Discussionmentioning
confidence: 99%
“…A histopatologia possibilita tipificar lesões neoplásicas em primárias ou secundárias (metastáticas), diferenciar e identificar alterações que levam ao glaucoma, bem como um possível acometimento ocular por doenças sistêmicas (Massa et al 2002.…”
Section: Introductionunclassified